Use Of Thin Flap In Reconstructive Surgery - Saha, Dr. Ila; Gupta, Dr. S.; Palle, Dr. N.; Ganguly, Prof. A. C. (Indian Journal of Plastic Surgery, 1984)
Method of planning and dissection of radically thin flap is described, and was utilised to cover the different areas of the body in 25 caases. Their results are analysed.